(3JWHjb HGSJNOGe HQfGeL (BMinitab ,Relase 14s - (3YOfGf OGhO eMeO(B, (3GdYPGQjs ((3YeGf(B:s (3OGQ LQjQ(B,s, 2010)
(3GdHjGfGJ h GdfeGPL (B: (3fehPL GdGfMOGQ GdHSjW , GdGfMOGQ GdeJYOO , GdJbOjQ HGSJOGe GdceHjhJQ, GdeTGcd GdbjGSjI (B: (3eTcdI GdJYOO GdNWj , GdQJHGW GdPGJj h eTcd YOe KHGJ JLGfS GdJHGjf , GdeJZjQGJ GdNGQLjI h GdOGNdjI GdeNJdaI RefG , JeGQjf GdfeGPL GdBfjI , GdJMjR GdBfj h eTcd GdJTNjU , WQb JbOjQ GdfeGPL GdBfjI (B.s
(3eQGLY U(B.189 (3; edGMb U(B191s
Keywords: (3GdEbJUGO GdQjGVjs; (3GdGbJUGO GdbjGSjs; (3GdJfHDs